Upaya Guru Dalam Meningkatkan Keaktifan Siswa Didalam Kelas Dan Implikasi Bagi Guru Masa Kini - Novita Prima Ningsih; Filmon Berek (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
This study discusses the teacher's efforts to increase student activity in the classroom and the implications for today's teachers. The purpose of this study was to find out the teacher's efforts to increase student activity in class and what are the inhibiting factors of teachers in increasing student activity in class. The type of research used is qualitative research with a descriptive approach. The techniques used by this researcher are case studies, descriptive, phenomenological, ethnographic, and biographical. As for the results of research conducted by researchers for more than 1 month, it can be concluded that the efforts made by the teacher in increasing student activity in the classroom and the implications for today's teachers are by providing motivation, using varied methods, using learning media, group discussions, giving good praise. reasonable, giving numbers or grades, creating a pleasant atmosphere, and giving assignments to students and factors that inhibit teachers in increasing student activity in class and the implications for today's teachers consist of two factors, namely internal and external, internal factors students do not have breakfast morning and students have bad habits and the external factors are the lack of motivation from parents and the lack of supporting books.